Cost benefit analysis of a web bag in a web warehouse: An analytical approach - BHOWMICK, Sourav S. (Institutional Knowledge at Singapore Management University, 2000)
Sets and bags are closely related structures and have been studied in relational databases. A bag is different from a set in that it is sensitive to the number of times an element occurs while a set is not. In this paper, we introduce the concept of web bag in the context of a web warehouse called Whoweda (Warehouse Of Weda Data) which we are currently building. Informally, a web bag is a web table which allows multiple occurrences of identical web tuples. Web bag helps to discover useful knowledge from a web table such as visible documents (or web sites), luminous documents and luminous paths. In this paper, we perform a cost-benefit analysis with respect to storage, transmission and operational cost of web bags and discussed issues and implication of materializing web bags as opposed to web tables containing distinct web tuples. We have computed analytically the upper and lower bounds for the parameters which affect the cost of materializing web bags.